2023
DOI: 10.1155/2023/1668663
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Movable Fluid Distribution in Tight Oil Reservoirs by NMR and Centrifugation

Abstract: The reservoir of Chang 7 Member of Yanchang Formation in the Ordos Basin is rich in tight oil resources, with well-developed micro-nanopore throats, strong heterogeneity, and complex fluid distribution characteristics. In this paper, a combination of nuclear magnetic resonance and centrifugation experiments is carried out to qualitatively and quantitatively analyze and evaluate the distribution characteristics of the movable fluid in Chang 7 reservoirs in Baibao Block. With different centrifugal forces, the NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, since the nuclear magnetic T 2 spectrum is easily affected by pore structure, fluid distribution in micropores, and fluid types, some logging interpretation methods developed based on NMR logging are not applicable in tight reservoirs [19,20]. Although the two-dimensional NMR logging includes more comprehensive information and has more advantages in fluid identification of tight sandstone reservoirs than one-dimensional NMR logging, it has not been widely used in many oilfields because of its high price and complex data processing process [21][22][23]. In terms of fluid identification by array acoustic logging, array acoustic logging can directly measure the P-wave velocity and S-wave velocity of reservoir rock and can calculate the elastic parameters reflecting the comprehensive properties of skeleton and pore fluid.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the nuclear magnetic T 2 spectrum is easily affected by pore structure, fluid distribution in micropores, and fluid types, some logging interpretation methods developed based on NMR logging are not applicable in tight reservoirs [19,20]. Although the two-dimensional NMR logging includes more comprehensive information and has more advantages in fluid identification of tight sandstone reservoirs than one-dimensional NMR logging, it has not been widely used in many oilfields because of its high price and complex data processing process [21][22][23]. In terms of fluid identification by array acoustic logging, array acoustic logging can directly measure the P-wave velocity and S-wave velocity of reservoir rock and can calculate the elastic parameters reflecting the comprehensive properties of skeleton and pore fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental research on formation water mobility, scholars often employ methods such as X-ray diffraction, scanning electron microscopy, and centrifugation combined with nuclear magnetic resonance [27][28][29]. For instance, Liu et al [17] and Wang et al [30] conducted nuclear magnetic resonance experiments to investigate the impact of microscopic pore structure on formation water mobility in tight reservoirs. They concluded that variations in throat types and the distribution of pore throat radii are the primary factors influencing the saturation of movable fluids.…”
Section: Introductionmentioning
confidence: 99%